Vigor and Viability Testing of Rice (Oryza sativa L.) Local Mutant Germplasm of Padang Pariaman through Gamma Irradiation - Henny Puspita Sari; Irfan Suliansyah; Indra Dwipa; Dini Hervani; Winda Purnama Sari; Fatardho Zudri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
As a genetic resource, local rice can provide insight into the inheritance of favorable traits. Local rice varieties have naturally been tested for resistance to pests and diseases, high yields, good rice quality (including class 1 quality), and a taste that people like, but also have some disadvantages, such as long life and high plant height that easily collapses. For this reason, the characteristics of local rice varieties that have these advantages are improved using the gamma-ray induced mutation technique. Before planting in the field, it is necessary to test the vigor and viability of local rice genotypes (Oryza sativa L.) Padang Pariaman seeds first. In this study, researchers used three different rice varieties, namely: